Stress characterization and support measures estimation around a coalmine tunnel passing through jointed rock masses: constraints from BEM simulation - Islam, Md. Kamrul; Islam, Md. Rafiqul (International Journal of Advanced Geosciences, 2016)
In the present research, the stress characterization around an unsupported coalmine tunnel passing through jointed rock masses was ana-lyzed and effective support system was calculated by BEM numerical simulations. The distribution and magnitudes of major and minor principal stress contours, mean stress, differential stress, total displacement, maximum shear strain, maximum shear stress contours around the tunnel are simulated by using the examine2D software. It is reasonable to mention that examine2D is a plane strain boundary element program for calculation of stresses and displacements around underground and surface excavation in rock. Modeling results reveal that the major principal stress (Ïƒ1) was about 13 MPa at the immediate roof of the tunnel that ultimately increased to 20 MPa toward the left side and right side. Mean stress contour value was 12 MPa at the immediate roof and 15 MPa toward the both rib sides. The distribution contour value of differential stress at the roof and rib sides were 16 MPa and 23 MPa, respectively. The contour values of the strength factor around the tunnel ranged from 0.51 to 1.02, which specify that the loosening zone would be extended up to 1.53 m towards the roof and 1.25 m at the sidewalls. The thickness (1.53 m) of loosening zone can be classified as soft or poor rock mass. In the immediate roof, floor and the both rib sides of the tunnel, the Spalling Criterion values ranged from 2.7 to 8.0 MPa, which indicate no potential for rock-burst around the tunnel. However, flexible support would be required to accommodate the dilatancy deformation during development period. Finally, the stiff support would be required to provide a strong supporting reaction and to maintain the long-term stability of the tunnel.